Icy affairs: Understanding recent advancements in the freezing and frozen storage of fish. Issue 2 (23rd January 2022) - Jia, Hui; Roy, Koushik; Pan, Jinfeng; Mraz, Jan
Abstract: Freezing methods have evolved over the last 30 years. This review states the effect of various freezing methods on the quality of fish and seafood. Freezing temperatures, freezing, and frozen storage temperatures were also analyzed and reviewed. The changes in the ice crystal, protein, and lipid affect the fish quality and nutritional value during freezing and frozen storage. Freezing methods when combined with various additives or preprocessing approaches help improve the efficacy of freezing and frozen storage. Several experimental or emerging methods also have positive effects on the products' quality. According to the metadata reanalysis of quality markers, freshly frozen fish using different freezing methods may vary much in terms of ice diameter, but not others. High pressure freezing or immersion freezing‐derived fish retains the best quality through frozen storage. More data are required on freezing methods (electrical‐assisted freezing, microwave‐assisted freezing, magnetic‐assisted freezing, radiofrequency‐assisted freezing, and the commercial's application and investment should be considered in the future. This review sheds light on finding a balanced initial shear force during freezing and the use of certain additives to control freezing‐related damages. Focusing on ice diameter alone may be futile (e.g., liquid N2 freezing). Future optimization of technologies should be in a way that several processes along the farm to fork such as freezing, frozen storage, thawing, thermal processing of fish, and even refabrication of food should mutually complement each other's needs to deliver safe and high‐quality fish to the consumer's plate, even after a prolonged shelf‐life.